Genetic instability assessed by telomere length and micronucleus in physicians exposed to anesthetics - Braz, Mariana Gobbo [UNESP]; Silva, Mariane A. P. [UNESP]; Figueiredo, Drielle B. S. [UNESP]; Aun, Aline G. [UNESP]; Marques, Lais S. K. [UNESP]; Lara, Juliana R. [UNESP]; Braz, Leandro Gobbo [UNESP] (Wiley, 2020)
This study evaluated both telomere length (TL) and micronucleus (MN) as indicators of genome instability in 40 anesthesiologists occupationally exposed to anesthetics and in 40 physicians without occupational exposure to anesthetics who were matched by age, sex, and lifestyle. Blood and buccal samples were collected from both groups at the same period. Anesthetic exposure assessment was performed. The studied groups were assessed regarding relative TL by quantitative polymerase chain reaction and MN by buccal MN assay. Mean trace concentrations of anesthetics were below two parts per million. No significant differences between groups were found for both biomarkers. However, MN frequency was slightly increased (1.9-fold; p =.094) in the exposed group compared to the control group and in the exposed males (2.4-fold; p =.090) compared to unexposed males. TL and age showed a significant negative correlation. Anesthetic occupational exposure below recommended levels is not associated with changes in TL and MN in anesthesiologists.
Keywords: anesthesiologists; inhalation anesthetics; micronuclei; occupational exposure; telomere